Peningkatan Kemampuan Berpikir Kritis Siswa Kelas III Pada Materi Operasi Pengurangan Model Teams Games Tournament - Syahruni Fariha Handayani; Siti Nur Elisa; Diana Ermawati (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This research aims to improve the learning outcomes and critical thinking abilities of class III students on subtraction operations material through the application of the Tems Gemes Tournament learning model. This type of research uses Class Action (PTK) which is carried out in 2 cycles. The data collection techniques used are planning, implementation, observation and reflection. The object of this research was class III students at SDN Pangendisan, totaling 16 students. The instruments in this research used observation, interviews and tests. This research shows that the application of the Teams Games Tournament model can improve students' learning outcomes and critical thinking abilities. The results of this research obtained that the average student learning outcomes in the pre-cycle were 23.9%, then increased in the first cycle to 70.24% with (KKM) of 67% and again increased in the second cycle, namely 83.57 with the category ( KKM) of 86%. With the learning results, it can be shown that students' thinking abilities in implementing the Teams Games Tournament model become more active, involved and able to solve mathematical problems. Thus, the Tems Games Tournament learning model improves learning outcomes and students' critical thinking skills in subtraction operations material. Based on the research results, it can be concluded that the Teams Games Tournament learning model can improve the Mathematics learning abilities of class III students at SDN Pangendisan.